Psychoanalysing evil: Sinason, V (ed) (1994) Treating survivors of satanist abuse. London & New York: Routledge. ISBN 0-415-10543-9. - Ivey, Gavin (PINS-Psychology in Society, 2026)
Of all the phenomena which today invoke the opprobrium and psycho-legal scrutiny of contemporary Westerners, child abuse is regarded as perhaps the most reprehensible. When this abuse includes an occult ritual element the moral revulsion increases exponentially. The reason is not hard to discover. The sadistic abuse of a child by an adult invokes the archetypal polarities of absolute innocence and absolute malevolence. When this emotionally charged moral duality is fuelled by the sinister spectre of satanic ritual involvement, the socio-psychological dimensions of the issue are eclipsed by the apocalyptic supernatural contest of good against evil. The abuser is no longer regarded as a mere social deviant, but in the popular imagination becomes a demonic instrument, no longer a fallen mortal, but rather the very incarnation of supernatural destructiveness.